The genetic architecture of growth traits in Salix matsudana under salt stress. (14th June 2017) - Zhang, Jian; Yuan, Huwei; Yang, Qingshan; Li, Min; Wang, Ying; Li, Yujuan; Ma, Xiangjian; Tan, Feng; Wu, Rongling
Abstract: Willow ( Salix ) is one of the most important ornamental tree species in landscape plants. One species, Salix matsudana, is widely used as a shade tree and border tree because of its soft branches and plump crown. Some varieties of S. matsudana were salt tolerant and could grow normally in coastal regions. However, the molecular mechanisms of salt tolerance for S. matsudana have been less clear. Here, we addressed this issue by performing a mapping experiment containing 195 intraspecific F1 progeny of S. matsudana, derived from salt-sensitive 'yanjiang' and salt-tolerant '9901', grown by cuttings in a 100 mM NaCl solution. Growth performance of these progeny under salt stress was investigated, displaying marked genotypic variability with the coefficients of variance of 28.64–86.11% in shoot and root growth traits. We further mapped specific QTLs contributing to these differences to the Salix genome. Of the 204 QTLs identified, a few were detected to explain a remarkably larger portion of the phenotypic variation than many others. Many detected QTLs were found to reside in the region of candidate genes of known biological function. The discovery of growth QTLs expressed under salt stress provides important information for marker-assisted breeding of salt tolerant Salix varieties and founds the basis for the application of S. matsudana in coastal afforestation. Abstract : Plant breeding: The salt in the willows Researchers in China have identified parts of the willow genome related to salt tolerance. Rongling Wu of the Beijing Forestry University and Pennsylvania State University and coworkers grew cuttings of 195 hybrid willows from a cross between a salt-tolerant strain and a salt-sensitive strain in a salty solution and measured their growth. Coupled with a genetic map, this enabled the team to identify 204 regions in the genome linked with salt tolerance. Comparison with corresponding regions in the well-characterized poplar genome revealed that the genes potentially related to salinity tolerance are involved in a variety of metabolic processes, including stress response and membrane repair. These findings will be valuable in efforts to breed or engineer salt-tolerant varieties of willow which can be used to green coastal areas and soils polluted with heavy metal salts.